The economics of religion in India - Iyer, Sriya (Harvard University Press, 2018)
Based on research conducted in India for over a decade, The Economics of Religion in India outlines the historical growth of religion and contemporary attitudes towards it in the country. The study of religion is related to broader themes of religious conflict and extremism, especially Hindu-Muslim riots since 1950. The book contributes to the economics of religion by discussing how religion relates to growing inequality in India, changes in demography, socio-economic status, and religious competition. The author presents original research findings from a survey of 600 Hindu, Muslim, Christian, Jain and Sikh religious organizations across seven Indian states with respect to their religious and nonreligious provision of such services as health and education. In addition, she discusses the introduction of mathematics, science, English, and computers into traditional religious curricula; and explores the marketing, communication, and branding of religion in India. Ultimately, the book aims to inform economic and social policy in countries with religiously pluralistic populations.--